Sex Differences in Mouse Models of Autism Spectrum Disorders: Their Potential to Uncover the Impact of Brain Sexual Differentiation on Gender Bias - Murta, Verónica (2023)
Autism spectrum disorder (ASD) is a neurodevelopmental condition with a prevalence rate of 2.78%, and it is characterized by deficits in sociability and communication and restricted patterns of interests and activities. Remarkably, this psychiatric disorder exhibits a pronounced gender bias, with 80% of children diagnosed with ASD being boys. In this review, we will present advancements in mouse models of ASD and their potential contributions to our understanding of the disorder. Wewill highlight how initial pre-clinical investigations focused solely on male mice due to the gender bias in ASD and explain why we believe that this approach might have had detrimental consequences regarding our understanding of ASD etiology and pathophysiology. We will highlight the evidence of two sensitive periods during brain development when differential exposure to gonadal hormones may result in sex differences in brain function and behavior: the perinatal period and the pre-pubertal period. Finally, we will suggest neuroinflammation as a feasible biological mechanism that may converge different ASD etiological factors and cellular mechanisms into a brain sexual differentiation context, thus accounting for the gender disparities observed in the disorder.